The effect of paper versus realized losses on subsequent risktaking - Meier, Philippe,Flepp, Raphael,Rüdisser, Maximilian,Franck, Egon (University of Zurich, Department of Business Administration, 2020)
In this paper, we test the realization effect, i.e., that risk-taking increases after a paper loss, whereas risk-taking decreases after a realized loss, using gambling data from a real casino. During a particular casino visit, losses are likely perceived as paper losses because the chance to offset prior losses remains effective until leaving the casino. However, when casino customers leave the casino, the final account balance is realized. Using individual-level slot machine gambling records, we find that risk-taking after paper losses increases during a visit and that this effect is more pronounced for larger losses. Conversely, risk-taking across multiple visits is not altered if the realized losses are comparatively small, whereas risk-taking is reduced if realized losses are comparatively large
10.5167/uzh-182628
Keywords: Arbeitspapier; Graue Literatur; decision making; realization effect; risk behavior; loss; field analysis